Evolutionary history of Spalacidae inferred from fossil occurrences and molecular phylogeny. (30th October 2019) - HE, Ya; Hu, Shuzhan; Ge, Deyan; Yang, Qisen; Connor, Thomas; Zhou, Caiquan
Abstract: The Spalacidae is a family of strictly subterranean rodents with a long evolutionary history. It is unclear how ecological changes have influenced the evolutionary history of these mammals, and the phylogenetic relationship of the subfamilies within Spalacidae is controversial. Through compiling fossil records, reconstructing molecular phylogeny from molecular data, determining the date of divergence, and analysing their geographical evolution based on molecular data and fossil taxa, we explore the origin and evolutionary process of Spalacidae in detail. Diversification within Spalacidae dates to the Late Oligocene, approximately 25 million years ago, based on molecular data. This family originated in South and East Asia in the Late Oligocene, and then split into four clades. The first clade includes Rhizomyinae, which was highly diversified in South Asia in the Early‐to‐Middle Miocene. Then Rhizomyinae from Asia migrated to northern Africa in multiple waves through the Afro‐Eurasian land bridge. Its range largely contracted in the Late Miocene, notably in Central Asia. The second clade includes the extinct Tachyoryctoidinae, which was confined to East and Central Asia, and survived from the Late Oligocene to the Late Miocene. The third clade includes Spalacinae, which have remained around the Mediterranean region since the Late Oligocene with slight trend of northward expansion. The fourth clade is Myospalacinae. Ancient genera of this subfamily in East Asia dispersed eastward during the Late Miocene and reached northern China and south‐east Russia. The general distribution pattern of Spalacidae has persisted since the Late Miocene. Extinction of Tachyoryctoidinae and clear range contraction of Rhizomyinae in Central and East Asia are likely to have resulted from increased aridification, while the slight northward expansion of Myospalacinae and Spalacinae since the Quaternary was probably a response to a similar northward expansion of suitable vegetation for these animals. Abstract : The phylogeny reconstruction and origination site inference of Spalacidae based on S‐DIVA. (a) The reconstructed phylogenetic tree and the inference results. The legend specifies the predefined areas used in the analyses. Solid lines show the branch of extant genera (in bold), and dotted branches show the placement of fossil genera with uncertainty. (b) The predefined areas used to infer the origination of Spalacidae, which was mapped on the annual average temperature (Bio 1) in the last glacial maximum (original layer downloaded from WorldClim, http://www.worldclim.org/past ), and the current distribution of Spalacidae (downloaded from the IUCN, http://oldredlist.iucnredlist.org/ ). Four predefined areas including (1): South and East Asia; (2) the Tibetan Plateau and inland arid regions of Central Asia; (3) south‐eastern Europe, the eastern Mediterranean area, and northernmost Africa; and (4) Central and East Africa. Dots show the distribution of fossils. The current geographical range of each of the three families of Spalacidae is indicated.